Radiation Resistance of Soil Azotobacter - Vela, Gerard R. (1965)
Vela, Gerard R. (School of Aerospace Medicine, Brooks Air Force Base, Tex.), and Orville Wyss. Radiation resistance of soil Azotobacter. J. Bacteriol. 89:1280–1285. 1965.—Quantitative recovery of Azotobacter from soils subjected to γ-radiation from a cobalt-60 source showed the soil populations to be much more highly resistant than isolates from such cultures grown on laboratory media. Even in the encysted state, the laboratory populations were reduced 10,000-fold by exposure to 200 kr, whereas the soil populations were not measurably reduced by that dose.